New insights into the history of the C‐14010 lactase persistence variant in Eastern and Southern Africa. Issue 4 (2nd December 2014) - Macholdt, Enrico; Slatkin, Montgomery; Pakendorf, Brigitte; Stoneking, Mark; Lewton, Kristi; Nalley, Thierra K.
ABSTRACT Lactase persistence (LP), the ability to digest lactose into adulthood, is strongly associated with the cultural traits of pastoralism and milk‐drinking among human populations, and several different genetic variants are known that confer LP. Recent studies of LP variants in Southern African populations, with a focus on Khoisan‐speaking groups, found high frequencies of an LP variant (the C‐14010 allele) that also occurs in Eastern Africa, and concluded that the C‐14010 allele was brought to Southern Africa via a migration of pastoralists from Eastern Africa. However, this conclusion was based on indirect evidence; to date no study has jointly analyzed data on the C‐14010 allele from both Southern African Khoisan‐speaking groups and Eastern Africa. Here, we combine and analyze published data on the C‐14010 allele in Southern and Eastern African populations, consisting of haplotypes with the C‐14010 allele and four closely‐linked short tandem repeat loci. Our results provide direct evidence for the previously‐hypothesized Eastern African origin of the C‐14010 allele in Southern African Khoisan‐speaking groups. In addition, we find evidence for a separate introduction of the C‐14010 allele into the Bantu‐speaking Xhosa. The estimated selection intensity on the C‐14010 allele in Eastern Africa is lower than that in Southern Africa, which suggests that in Eastern Africa the dietary changes conferring the fitness advantage associated with LP occurred some time after the origin of the C‐14010 allele. Conversely, in Southern Africa the fitness advantage was present when the allele was introduced, as would be expected if pastoralism was introduced concomitantly. Am J Phys Anthropol 156:661–664, 2015. © 2014 Wiley Periodicals, Inc.